2004
DOI: 10.1074/jbc.m314086200
|View full text |Cite
|
Sign up to set email alerts
|

Pre-binding of Small Protein B to a Stalled Ribosome Triggers trans-Translation

Abstract: To rescue stalled ribosomes, eubacteria employ a molecule, transfer messenger RNA (tmRNA), which functions both as a tRNA and as an mRNA. With the help of small protein B (SmpB), tmRNA restarts protein synthesis and adds by the trans-translation mechanism a peptide tag to the stalled protein to target it for destruction by cellular proteases. Here, the cellular location and expression of endogenous SmpB were monitored in vivo. We report that SmpB is associated with 70S ribosomes and not in the soluble fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
97
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(111 citation statements)
references
References 34 publications
12
97
1
1
Order By: Relevance
“…According to cryo-EM data, SmpB is bound to tmRNA in the pre-accommodation complex (17). Recently, it was found that SmpB can also be bound to the ribosome (16) and that two molecules of SmpB pre-bound to one ribosome facilitate the accommodation of tmRNA in an in vitro system. These data indicate that SmpB plays an essential role at the stage of the initiation of trans-translation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to cryo-EM data, SmpB is bound to tmRNA in the pre-accommodation complex (17). Recently, it was found that SmpB can also be bound to the ribosome (16) and that two molecules of SmpB pre-bound to one ribosome facilitate the accommodation of tmRNA in an in vitro system. These data indicate that SmpB plays an essential role at the stage of the initiation of trans-translation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that all SmpB molecules are bound to ribosomes within the cell. Moreover, one ribosome can bind two protein molecules that remain bound to the ribosome even after the transfer of undersynthesized peptide to tmRNA (16). SmpB was also found to be the partner of tmRNA on entering the ribosome during the pre-accommodation stage (17).…”
mentioning
confidence: 94%
“…The SmpB protein is an essential component for trans-translation in vivo, responsible of a variety of actions in the course of the mechanism. It binds with high affinity to tmRNA in vivo, 9 protects it from degradations in the cells (3-fold shorter half-life of tmRNA in the Δsmpb cells compared with wild-type cells, Hallier et al 18 ) and enhances its alanylation efficiency.…”
Section: Smpb As the Handyman Of Tmrna During Trans-translationmentioning
confidence: 99%
“…While SmpB is required for ala-tmRNA to bind the stalled ribosomes, the opposite is not true: SmpB can bind tightly to 70S ribosomes in the absence of tmRNA, either in vitro or in vivo. 18,19 This raises the question of the chronology of the early events leading to trans-translation initiation. Is a pre-formed Figure 1.…”
Section: Smpb As the Handyman Of Tmrna During Trans-translationmentioning
confidence: 99%
“…Lorsque des ribosomes en cours de traduction parviennent à l'extrémité d'ARN messagers défectueux, une petite protéine basique appelée petite protéine B ou SmpB [11], possédant certaines analogies avec des protéines du ribosome, s'associe avec les ribosomes bloqués [12,13]. Ce positionnement prépare l'arrivée de l'ARNtm.…”
Section: La Trans-traduction Est Gouvernée Par Un Arn Hybride Et Par unclassified